Peran Komunikasi Islam dalam Membangun Representasi Sosial dan Struktur Kekuasaan pada Tradisi Ruwahan di Sendangduwur - Intihaul Khiyaroh; Shofia Elviana; Hanifah Rihadhatul Aisyah; Rafi Ramadhani (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2025)
The Ruwahan tradition in Sendangduwur Village, Paciran District, Lamongan Regency, is a form of local cultural preservation imbued with Islamic values introduced through the cultural da’wah of Sunan Sendangduwur. Islamic communication in this tradition plays a crucial role in shaping the social representation of the community through rituals of sedekah (almsgiving) and selametan (communal feast), which include prayers for deceased relatives, while also reinforcing religious and social power structures within the community. Sunan Sendangduwur’s da’wah approach internalizes Islamic values peacefully and tolerantly alongside Javanese culture, making the Ruwahan tradition an effective communication medium for maintaining social identity and religious authority in the coastal Lamongan area. The regularly held Ruwahan Festival not only strengthens social solidarity but also asserts the existence of power structures rooted in culturally adapted Islamic values. Thus, Islamic communication through the Ruwahan tradition in Sendangduwur functions as a strategic means to build and represent harmonious and sustainable social relations and power structures in the local society.